GROWTH AND PRODUCTION OF KIWANO IN THE OPEN FIELD IN THE SOUTH OF WESTERN SIBERIA - N. B. Naumova; Y. V. Fotev; G. A. Bugrovskaya; N. T. Vladimirova; S. B. Drozdova; R. P. Makarikova; T. V. Nechaeva; O. A. Savenkov; N. V. Smirnova; A. S. Chumbaev; V. P. Belousova (Овощи России, 2016)
Kiwano plants, or horned cucumber (Cucumis metuliferus E. Mey ex Naudin) was grown in the open field in several experimental plots in the south of West Siberia (54,95025 N, 83,09763 E). Fruits production was correlated with night air temperature sum and soil organic matter content, reaching the maximum of 2.7 kg (fresh phytomass) per plant. Fruit size and some basic juice characteristics were similar to those of kiwano fruits grown elsewhere in the world. The vegetative phytomass grown was correlated with day air temperature sum, being practically independent of soil chemical properties. Thus kiwano can be recommended as a crop to be grown in the open field in the south of West Siberia and other regions of Russia with similar soil and environmental conditions.